Occupational Determinants of HDL Cholesterol among Bauxite Mining Workers - Sumardiyono Sumardiyono; Ade Kurdiman; Ardian Yoga Bharata (Universitas Airlangga, 2026)
Introduction: High-density lipoprotein (HDL) cholesterol is recognized to play a protective role against cardiovascular disease and its regulation is related to occupation and lifestyle. The determinants of HDL cholesterol in bauxite mining workers at private bauxite mining company in Indonesia were studied. Methods: This is a cross-sectional study that relies on secondary data obtained from medical check-ups from June 2023 to January 2024. A total of 567 workers were initially identified, with 536 workers having complete data available for analysis. Age, body mass index (BMI), resting heart rate (as a biological measure of physical activity), and smoking status were the independent variables, and HDL cholesterol was the dependent variable. All the standard statistical assumptions were tested, and multiple linear regression analysis was used if all the requirements were fulfilled. Results: HDL cholesterol showed significant negative associations with smoking (β = −0.169; p < 0.001), BMI (β = −0.129; p = 0.003), and age (β = −0.112; p = 0.009), but no significant association with resting heart rate (β = −0.023; p = 0.593). The model accounted for 5.6% of the variance in HDL cholesterol, and smoking proved to be the most important negative predictor. Conclusion: Smoking, nutritional status, and age are the main factors that determine HDL cholesterol levels in bauxite mining workers. The findings underscore the need for occupational health promotion, particularly in smoking cessation and weight management, in order to lessen the cardiovascular disease risk.